MO590GUT HEALTH INTERVENTIONS IN CHRONIC KIDNEY DISEASE: ACCEPTABILITY AND FEASIBILITY OF OF SYNBIOTIC SUPPLEMENTATION. (29th May 2021) - McFarlane, Catherine; Krishnasamy, Rathika; Stanton, Tony; Savill, Emma; Kelly, Jaimon T; Snelson, Matthew; Mihala, Gabor; Morrison, Mark; Johnson, David W; Campbell, Katrina L
Abstract: Background and Aims: Synbiotics, co-administered prebiotics and probiotics, have emerged over the last decade as an innocuous intervention targeting the microbial generation of the uraemic toxins, indoxyl sulphate (IS) and p -cresyl sulphate (PCS). However, most trials to date are of short duration (2-24 weeks). In order to inform translation into clinical practice, it is imperative to consider the efficacy of synbiotic supplementation as a long-term intervention. The aims of this study were to evaluate the feasibility and acceptability (including symptoms and adherence) of long-term synbiotic supplementation in adults with chronic kidney disease (CKD), as well as explore the perspectives of these patients on nutrition supplementation for gut health, including strategies to optimise adherence in practice. Method: SYNERGY II was a double-blind randomised controlled trial in adults (>18years) with stage 3-4 CKD over 12 months. The intervention comprised of daily prebiotic powder (2 x 10g/day resistant starch) and probiotic supplementation (single sachet of 6g/day multi strain 4.5x10 11 CFU) or placebo control (waxy maize powder and a sachet of maltodextrin). Adherence to nutrition supplementation was defined as participants consuming >80% of the prescribed sachets/powder. Symptoms were monitored via Gastrointestinal Symptom Rating Scale (GSRS) and Bristol Stool Score (BSS). Semi-structured interviews were conducted in person or by telephone with a sample of 30 participants at the completion of the intervention. The interviews explored experiences and perspectives regarding frequencies, timing and difficulties experienced with each aspect of the intervention and overall perceptions of the intervention as a strategy to improve gut health. Results: Sixty-eight participants [66% male, median age 70 (IQR 58-75) years] were consented and randomised to either intervention or control groups, with a mean estimated glomerular filtration rate of 34 ± 11 mL/min/1.73m 2 . A total of 56 participants (82%) completed the 12-month intervention with no differences in withdrawals between groups (p=0.6). One participant from each group withdrew at week 2, citing palatability of the study product as the reason for withdrawal. Overall adherence to study supplementation was excellent in both intervention and placebo groups [median intake 92.1% (85.9-95.2%) placebo versus 89.5% (84.4-94.5%) synbiotic; P=0.4)]. Overall, there was no significant change from baseline to end of study visit for mean BSS (3.6 ± 1.4 to 3.6 ± 1.4 placebo versus 3.6 ± 1.1 to 4.1 ± 1.2 synbiotic, P=0.13), mean bowel movements (1.3 ± 0.6 to 1.6 ± 0.9 placebo versus 1.3 ± 0.6 to 1.8 ± 1.0 synbiotic, P=0.70) or GSRS [1.3 (1.1 - 1.9) to 1.3 (1.1 - 1.5) placebo versus 1.1 (1.1 - 1.5) to 1.3 (1.1 - 1.5) synbiotic, P=0.83]. Acceptability components described by participants were appreciating convenience and improving health and well-being. Participants discussed the following feasibility components: integrating easily into lifestyle and social accountability. Tablets or capsules were the preferred supplement formulation with a probiotic drink made from a SCOBY (synbiotic culture of bacteria and yeast) the least preferred. Conclusion: Among adults with stage 3-4 CKD, synbiotic supplementation is a well-tolerated and acceptable form of nutrition supplementation. People with CKD would prefer nutrition supplements to be formulated as a tablet or capsule, which is an important consideration when translating into clinical practice.